Encountering apartheid publics: an essay film on Hendrik Verwoerd as public symbol 1958-1966 and implications for counter-publics today. - Effendi, Karima (University of the Witwatersrand, Johannesburg, 2023)
The policies of separate development under Verwoerd created the material conditions for apartheid and capitalism to thrive, but it's the hypothesis of this project that the pomp and ceremony, the suit, his speeches and performative statecraft, created the affective conditions for his thinking to make its way from the past into our present-time. This is a discursive inquiry that draws on political theory, psychoanalysis, feminist theory and essayistic film theory to explore how the slipperiness of apartheid discourse makes it impossible to counter it on its own terms. Verwoerd symbolised a pernicious ‘covering over’ of irreconcilable ambiguities in apartheid discourse that was used to construct and stabilise whiteness against ‘other’ constitutive subject formations. The second part of the creative project is an essay film, Verwoerd’s Smile, that uses an ‘apartheid’ and colonial archive to attempt to show up its own discriminatory logic. The film’s failure in doing this has a productive value that is instructive for understanding how the cloak of invisibility that shrouds whiteness from being seen doing its work, also protects it from being dismantled. Understanding this has implications for radical projects concerned with undoing apartheid.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Film and Television to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: Verwoerd’s Smile, separate development, essay, film, apartheid discourse, feminist theory, colonial archive, affect; SDG-16: Peace, justice and strong institutions